Farm Boys Lives of Gay Men from the Rural Midwest - Fellows, Will (The University of Wisconsin Press, 1998)
Homosexuality is often seen as a purely urban experience, far removed from rural and small-town life. Farm Boys undermines that cliché by telling the stories of more than three dozen gay men, ranging in age from 24 to 84, who grew up in farm families in the midwestern United States. Whether painful, funny, or matter-of-fact, these plain-spoken accounts will move and educate any reader, gay or not, from farm or city.